Synthesis of 7-Pentafluorophenyl-1H-indole: An Anion Receptor for Anion–π Interactions - Sun, Zhan-Hu; Albrecht, Markus; Giese, Michael; Pan, Fangfang; Rissanen, Kari (Synlett, 2014)
7-Pentafluorophenyl-1H-indole has the potential to be a key compound for the investigation of anion–π interactions in solution. Unfortunately, it was not possible to obtain it by aryl–aryl coupling reaction. Finally, it has been prepared by Bartoli indole synthesis. The key compound as well as analogues were submitted to preliminary studies of anion binding. Single crystals of two key receptors were obtained.
Keywords: Bartoli indole synthesis; receptors; halides; indoles; molecular recognition